Biomarkers in patients with heart failure and central sleep apnoea: findings from the SERVE‐HF trial - Ferreira, João Pedro (ESC Heart Fail, 2020)
AIMS: The Treatment of Sleep‐Disordered Breathing with Predominant Central Sleep Apnoea by Adaptive Servo Ventilation in Patients with Heart Failure trial investigated the effects of adaptive servo‐ventilation (ASV) (vs. control) on outcomes of 1325 patients with heart failure and reduced ejection fraction (HFrEF) and central sleep apnoea (CSA). The primary outcome (a composite of all‐cause death or unplanned HF hospitalization) did not differ between the two groups. However, all‐cause and cardiovascular (CV) mortality were higher in the ASV group. Circulating biomarkers may help in better ascertain patients' risk, and this is the first study applying a large set of circulating biomarkers in patients with both HFrEF and CSA. METHODS AND RESULTS: Circulating protein‐biomarkers (n = 276) ontologically involved in CV pathways, were studied in 749 (57% of the trial population) patients (biomarker substudy), to investigate their association with the study outcomes (primary outcome, CV death and all‐cause death). The mean age was 69 ± 10 years, and > 90% were male. The groups (ASV vs. control and biomarker substudy vs. no biomarker) were well balanced. The “best” clinical prognostic model included male sex, systolic blood pressure < 120 mmHg, diabetes, loop diuretic, cardiac device, 6‐min walking test distance, and N‐terminal pro BNP as the strongest prognosticators. On top of the “best” clinical prognostic model, the biomarkers that significantly improved both the discrimination (c‐index) and the net reclassification index (NRI) of the model were soluble suppression of tumorigenicity 2 for the primary outcome; neurogenic locus notch homolog protein 3 (Notch‐3) for CV‐death and all‐cause death; and growth differentiation factor 15 (GDF‐15) for all‐cause death only. CONCLUSIONS: We studied 276 circulating biomarkers in patients with HFrEF and central sleep apnoea; of these biomarkers, three added significant prognostic information on top of the best clinical model: soluble suppression of tumorigenicity 2 (primary outcome), Notch‐3 (CV and all‐cause death), and GDF‐15 (all‐cause death).